Undulative induction formers of picosecond electron bunches - Kulish, V.V.; Gubanov, I.V.; Orlova, O.A. (Вопросы атомной науки и техники, 2001)
The basic physical mechanism and the design idea of a new type of Undulative Induction Formers (UNIFs or EH-formers) of especially short intensive electron bunches are proposed and studied. The characteristic feature of the proposed EH-former is the employing of nonstationary crossed linearly polarized electrical and magnetic undulative fields (EH-fields). Namely, the EH-former turns out to be "opened" for an electron beam only during a very short (picosecond) time interval. A possibility to form rather intensive picosecond electron bunches is shown. Including, the picosecond bunches with a number of electrons in each bunch ~ 10⁸÷10¹⁰.